ENT 530 Social Media Report: Delisio Pop Oats / Syafawati Che Ismail - Che Ismail, Syafawati (2021)
Delisio Pop Oats is an online based entrepreneurship that are from Bumiputera. This Product is an innovative instant oat that combine other ingredient especially nuts to different flavors. There are 5 flavor which is Strawberry, Banana, Rose Hazelnut, Chocolate, and Vanilla. The reason why I choose this product is because, this product consider as new for me and I really like the idea of combining other good ingredient into the oats. The chosen ingredients also very suitable for every flavor and also very appetizing. Then, I apply to be a dropshipper from Iryani Azwa, one of the agent as I am interested to promote the product. RM2 commission will be given for every purchase sold per box. She also guide me on how to promote, provide product’s details, customer satisfaction, and what to do if buyer wants to buy. Then I create an account for Facebook page and start doing some product promoting.